Local Government Innovations Related to the Application of Visionary Leadership and Super Leadership Styles - et.al, Nur Wahid (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze Local Government Innovations Related to the Application of Visionary and Super Leadership Leadership Styles. The approach used in this study is a qualitative approach. Data collection was carried out through observation and interviews. Activities such as data condensation, display data and conclusion drawing and verification. The results showed that the sustainability of innovation in North Luwu Regency which consists of legislative, executive, human resource, environment, technology, and community support in general has received a positive response so that the sustainability of innovation in North Luwu Regency is not in doubt. service improvement, process innovation, administrative innovation, systems innovation, conceptual innovation, and radical innovation. A number of types of innovations in North Luwu Regency have been implemented. The innovation that was born in North Luwu Regency is inseparable from the application of the Visionary leadership and Super leadership styles. Leadership innovation Visionary Leadership and Super leadership in terms of the types of innovation have met the type or types of innovation in the public sector.